A Comparative Analysis of Kali Pepe-Tirtonadi Weir and Japan’s Nagara River for Water-Based Tourism Development - Purwoko Ajie; Octaviano Dwiyan Putra; Satrya Paramanandana; Dannis Ni'matussyahara; Srimaryani Srimaryani; Raden Roro Ratnasari Dwi Riyanti; Desi Fitri Yani (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
The COVID-19 pandemic has receded from Indonesia, yet it has left enduring historical impacts, particularly on the economic sector, with tourism being one of the affected areas. Post-pandemic recovery has witnessed the emergence of numerous new locations and destinations, particularly water tourism sites, as part of tourism development initiatives. Through researcher observations via surveys and field observations in the Tirtonadi Weir area and Kali Pepe flow, several issues have been identified, including inadequate supporting facilities, suboptimal water flow circulation, less-than-optimal vegetation along the riverbanks, and pollution from inorganic waste in the river. This study adopts a qualitative comparative approach and employs SWOT analysis to compare the Kali Pepe-Tirtonadi Weir in Surakarta with the Nagara River in Japan. Data collection techniques include observation, literature review (books, journals, articles, YouTube videos, magazines, and newspapers), and documentation. Following data collection, a systematic qualitative and SWOT analysis is conducted. The findings reveal differences in management approaches between the Kali Pepe-Tirtonadi Weir and the Nagara River in Japan, attributed to long-term tourism planning, revitalization processes, and river management carried out by policymakers. It is anticipated that the Tirtonadi Weir and the Kali Pepe Stream can evolve into water tourism destinations, serving as new tourism icons in Surakarta City.